Correction to: Skin cancer risk perception and sun protection behavior at work, at leisure, and on sun holidays: a survey for Danish outdoor and indoor workers - Kasper Grandahl; Kristina Sophie Ibler; Gunnar Hellmund Laier; Ole Steen Mortensen (Komiyama Printing Co. Ltd, 2018)
Following publication of the original article [1], it was highlighted that Table 3 contained an error.